Ceramic tile adhesive as well as preparation method and application thereof
By combining anhydrous gypsum, beta gypsum with cement, and using calcium oxide and alum as an initiator, the problems of insufficient bonding strength and slow hardening speed of ceramic tile adhesive are solved, and efficient construction and firm adhesion effect are achieved.
Patent Information
- Application Number
- CN202411735428.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The bonding strength of existing ceramic tile glue is insufficient and the hardening speed is slow, which affects construction efficiency and adhesive quality.
Anhydrous gypsum, β-gypsum and cement are used as the gelling system, and calcium oxide and alum are used as the exciter to adjust the initial settable time of the ceramic tile glue and improve the bonding strength and construction efficiency.
It achieves high strength and appropriate hardening time of ceramic tile glue, improves construction efficiency and adhesion quality, and ensures firm bonding between the tile and the substrate.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a tile adhesive and a preparation method and application thereof. Background Art
[0002] Tile adhesive, also known as ceramic tile adhesive, is mainly used to stick ceramic tiles, facing tiles, floor tiles and other decorative materials. It is widely used in finishing and decoration places of interior and exterior walls, floors, bathrooms, kitchens and other buildings.
[0003] Most of the traditional tile adhesives in my country are ordinary mortars with cement as the main bonding component. However, general bonding mortars have great defects, such as excessive brittleness and insufficient flexibility, high compressive strength, but low flexural strength and bonding strength, high elastic modulus and poor deformation ability. Polymer modification can make cement-based bonding materials have good performance, but the existing polymer-type tile adhesives have a long curing time, which is not conducive to construction workers and reduces work efficiency; while adding accelerators and other additives to the raw materials, but ignoring their adhesive strength, the quality cannot be guaranteed under the conditions of rapid setting, resulting in unqualified adhesive strength and flexibility, poor weather resistance, easy cracks, or subsequent hollowing, leading to shedding.
[0004] Therefore, there is an urgent need to develop a tile adhesive with high bonding strength and moderate hardening speed to meet consumers' requirements for tile bonding strength and pasting construction speed. Summary of the invention
[0005] In view of the technical problems existing in the background technology, the present application provides a tile adhesive and a preparation method and application thereof, aiming to solve the technical problems of the existing tile adhesive having insufficient strength, slow hardening speed and long actual drying period.
[0006] In a first aspect, an embodiment of the present application provides a tile adhesive, which includes, by weight, 20 to 40 parts of cement, 30 to 50 parts of anhydrous gypsum, 20 to 25 parts of beta gypsum, 4 to 6 parts of activator, 0.5 to 2 parts of retarder, 0.5 to 2 parts of water retaining agent and 2 to 6 parts of cross-linking agent; wherein the activator includes calcium oxide and alum.
[0007] In the technical solution of the embodiment of the present application, anhydrous gypsum, β-gypsum and cement are compounded as a cementing system, which can improve the overall strength of the tile adhesive; at the same time, calcium oxide and alum are selected as activators to stimulate the anhydrous gypsum. When the hydration reaction occurs, the coagulation speed can be adjusted, thereby obtaining a tile adhesive with higher strength and controllable hardening time.
[0008] In some embodiments, the mass ratio of calcium oxide to alum is (1-5):(1-5).
[0009] In this embodiment, the amount of calcium oxide and alum will affect the hydration rate of anhydrous gypsum, thereby affecting the initial and final setting time of tile adhesive. By controlling the amount of calcium oxide and alum within a reasonable range, it is convenient to regulate the initial and final setting time of tile adhesive. Among them, if the amount of calcium oxide is too much, the initial setting time and final setting time of tile adhesive are shortened, which will cause the hardening speed of tile adhesive to be too fast, resulting in a weak bond between tile adhesive and tile or base surface, thereby affecting the quality and durability of paving; and if the amount of calcium oxide is too little, the final setting time of tile adhesive increases, affecting the construction efficiency. If the amount of alum is too much, the initial setting time of tile adhesive is shortened; and if the amount of alum is too little, the initial and final setting time of tile adhesive increases, resulting in extended construction time, affecting construction efficiency.
[0010] In some embodiments, the mass ratio of calcium oxide to alum is 2:3.
[0011] In this embodiment, by controlling the mass ratio of calcium oxide and alum contained in the tile adhesive to 2:3, a tile adhesive with more suitable initial and final setting times can be obtained. When the tile adhesive is used, on the one hand, the construction efficiency can be improved, and on the other hand, the tile adhesive has better bonding strength.
[0012] In some embodiments, the cement is one or more of sulphoaluminate cement, silicate cement, and aluminate cement.
[0013] In this embodiment, the tile adhesive with higher strength and better hardening time can be obtained by compounding anhydrous gypsum with the above-mentioned cement.
[0014] In some embodiments, the anhydrite is type II anhydrite with a mesh size of 600-1300 meshes.
[0015] According to the different hydration activities of anhydrous gypsum, anhydrous gypsum can be divided into type I, type II and type III, among which type I anhydrous gypsum only exists at a temperature higher than 1180°C, type III anhydrous gypsum easily absorbs steam in the air and is converted into β-hemihydrate gypsum, and type II anhydrous gypsum has higher strength and hardness than hemihydrate gypsum. In this embodiment, the cementitious system formed by compounding type II anhydrous gypsum with cement has better strength. At the same time, the particle size of anhydrous gypsum will affect the excitation effect of the stimulator on it. If the particle size of anhydrous gypsum is too small, the hydration reaction rate will be too fast, and the crystals obtained after the hydration reaction will be small. Due to the small crystals and large specific surface area, the amount of water used in the standard consistency of slurry needs to be increased, resulting in a larger porosity after the tile adhesive is hardened, and then the strength will decrease; if the particle size of anhydrous gypsum is too large, the hydration reaction rate will be slow, and it will easily lead to the presence of unhydrated anhydrous gypsum inside the tile adhesive. The residual anhydrous gypsum will be hydrated in the later stage of the hardening of the tile adhesive, which will induce the expansion and cracking of the tile adhesive, thereby affecting the long-term performance of the tile adhesive.
[0016] In some embodiments, the retarder is a protein retarder; and / or the water retaining agent is a cellulose ether compound; and / or the cross-linking agent is one or more of a silane coupling agent and a titanate coupling agent.
[0017] In this embodiment, the retarder can slow down the hardening speed of cement and anhydrous gypsum, so that there is more sufficient operation time during construction, the water retaining agent can promote the complete hydration of anhydrous gypsum, and the cross-linking agent can fully combine the anhydrous gypsum with cement and other additives, so that alkali and salt cannot migrate to the surface with water, thereby reducing the alkali return phenomenon.
[0018] In some embodiments, the tile adhesive includes 40 parts of cement, 50 parts of anhydrous gypsum, 25 parts of beta gypsum, 5 parts of activator, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0019] In this embodiment, by controlling the mass ratio of cement, anhydrous gypsum, beta gypsum, activator, retarder, water retaining agent and cross-linking agent to 40:50:25:5:1.25:1.25:3.5, the tile adhesive can obtain better strength and more suitable initial and final setting time.
[0020] In a second aspect, an embodiment of the present application provides a method for preparing the tile adhesive as described in the first aspect, comprising the following steps: The anhydrous gypsum, beta gypsum, activator, retarder, water retaining agent and cross-linking agent are uniformly mixed to obtain a mixture; Mix the mixture with cement evenly to obtain tile adhesive.
[0021] In the technical solution of the embodiment of the present application, anhydrous gypsum, beta gypsum, an activator and other additives are first mixed to obtain a mixture, wherein the activator in the mixture can activate the activity of the anhydrous gypsum to make it produce cementing properties. Thereafter, after the mixture is mixed with cement, the activated anhydrous gypsum contained in the mixture can form an anhydrous gypsum-cement double-bonding material with cement, and the anhydrous gypsum-cement double-bonding material has the effects of adjusting the hardening speed of tile adhesive, improving the durability of tile adhesive, and enhancing its bonding strength with tiles.
[0022] In a third aspect, an embodiment of the present application provides an application of the tile adhesive as described in the first aspect, comprising: uniformly mixing the tile adhesive and water to obtain a particle-free paste, and then pasting the tiles; wherein the mass ratio of the tile adhesive to water is 1:(0.2~0.6).
[0023] In the technical solution of the embodiment of the present application, the ceramic tile adhesive is mixed with water to paste the ceramic tiles, so it has the characteristics of strong bonding force and high construction efficiency. Among them, by controlling the amount of ceramic tile adhesive and water in a reasonable range, the consistency and fluidity of the mixture during mixing are guaranteed, so that the ceramic tile adhesive can not only be well bonded with the ceramic tile and the base surface during construction, but also can bear the weight of the ceramic tile before initial setting without flowing or collapsing. If the amount of water is too large and the fluidity is too high, it will be difficult for the ceramic tile to be bonded with the base surface, and a good bonding effect cannot be achieved; if the amount of water added is too low, the viscosity will be high, which may cause unevenness in the hardening process of the ceramic tile adhesive, affecting the performance and construction quality of the ceramic tile adhesive.
[0024] In some embodiments, the initial setting time of the tile adhesive during the application process is 5~30min, the final setting time is ≤180min, the original tensile bonding strength is 1.2~1.4MPa, the tensile bonding strength after immersion in water is 0.8~1.0MPa, the tensile bonding strength after heat aging is 1.1~1.3MPa, the tensile bonding strength after freeze-thaw cycles is 1.0~1.2MPa, the tensile bonding strength after airing for 20min is 0.6~0.85MPa, and the sliding distance of a 300g tile in 30 minutes is 0.15~0.25mm.
[0025] In this embodiment, the tiles are bonded by using the tile adhesive as described in the first aspect, so that the tiles have a suitable setting time and can achieve a firm bonding effect.
[0026] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION
[0027] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0029] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0030] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0031] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0032] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0033] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0034] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0035] The tile adhesive in the prior art has qualified strength but its setting time is relatively long. During the setting process of the adhesive, displacement or lateral deformation occurs when laying the tiles, and the tiles need to be re-laid, which is not only not conducive to the construction of the construction workers, but also reduces the work efficiency. However, when adding auxiliary agents such as accelerators to the raw materials, the adhesive strength is ignored, and its quality cannot be guaranteed under the condition of rapid setting, resulting in unqualified adhesive strength and flexibility, and poor weather resistance.
[0036] In order to solve the technical problems of insufficient bonding strength and slow hardening speed of existing tile adhesives, the present application provides a tile adhesive and a preparation method and application thereof, wherein by using anhydrous gypsum, β-gypsum and cement as bonding materials, not only a strong bonding layer can be formed, but also the initial and final setting time can be reduced, thereby improving the bonding strength between the tile and the substrate and improving the construction efficiency.
[0037] In a first aspect, an embodiment of the present application provides a tile adhesive, which includes, by weight, 20 to 40 parts of cement, 30 to 50 parts of anhydrous gypsum, 20 to 25 parts of beta gypsum, 4 to 6 parts of activator, 0.5 to 2 parts of retarder, 0.5 to 2 parts of water retaining agent and 2 to 6 parts of cross-linking agent; wherein the activator includes calcium oxide and alum.
[0038] In the technical solution of the embodiment of the present application, anhydrous gypsum, β-gypsum and cement are compounded as a cementing system, which can improve the overall strength of the tile adhesive; at the same time, calcium oxide and alum are selected as activators to stimulate the anhydrous gypsum, so that when the hydration reaction occurs, the coagulation speed can be adjusted, thereby obtaining a tile adhesive with higher strength and controllable hardening time. Among them, if the amount of cement and anhydrous gypsum is too much, the hydration reaction rate will slow down, thereby increasing the initial and final setting time of the tile adhesive. If the amount of cement and anhydrous gypsum is too little, the hydration reaction rate will be accelerated, resulting in a shortened initial setting time, and it is impossible to ensure sufficient construction operation time; at the same time, β-gypsum will also stimulate the anhydrous gypsum. If the amount of β-gypsum is too much, the hydration rate of the anhydrous gypsum will be accelerated, shortening the initial setting time of the tile adhesive. If the amount of β-gypsum is too little, the hydration reaction rate of the anhydrous gypsum is too slow, resulting in an increase in the initial setting time of the tile adhesive; if the amount of activator is too much, the hydration reaction rate of the anhydrous gypsum will be too fast, shortening the initial and final setting time. If the amount of activator is too little, the hydration reaction of the anhydrous gypsum cannot be effectively promoted, which will increase the initial and final setting time of the tile adhesive and affect the construction efficiency.
[0039] Furthermore, in some embodiments, the mass ratio of calcium oxide to alum is (1-5): (1-5).
[0040] In the technical scheme of the embodiment of the present application, the amount of calcium oxide and alum will affect the hydration rate of anhydrous gypsum, and then affect the initial and final setting time of tile adhesive. By controlling the amount of calcium oxide and alum within a reasonable range, it is convenient to regulate the initial and final setting time of tile adhesive. Among them, if the amount of calcium oxide is too much, the initial setting time and final setting time of tile adhesive are shortened, that is, the hardening speed of tile adhesive will be too fast, resulting in a weak bond between tile adhesive and tile or base surface, thereby affecting the quality and durability of paving; and if the amount of calcium oxide is too little, the final setting time of tile adhesive increases, affecting the construction efficiency. If the amount of alum is too much, the initial setting time of tile adhesive is shortened; and if the amount of alum is too little, the initial and final setting time of tile adhesive increases, resulting in an extension of construction time, affecting construction efficiency. The mass ratio of calcium oxide to alum can be 1:1, 1:2, 1:3, 1:4, 1:5, 2:1, 2:3, 3:4 or other ratios within this range.
[0041] Further, in some embodiments, the mass ratio of calcium oxide to alum is 2:3.
[0042] In the technical solution of the embodiment of the present application, by controlling the mass ratio of calcium oxide and alum contained in the tile adhesive to 2:3, a tile adhesive with a more suitable initial and final setting time can be obtained. When the tile adhesive is used, on the one hand, the construction efficiency can be improved, and on the other hand, the tile adhesive has better bonding strength.
[0043] Furthermore, in some embodiments, the cement is one or more of sulphoaluminate cement, silicate cement, and aluminate cement.
[0044] In the technical solution of the embodiment of the present application, a tile adhesive with higher strength and better hardening time can be obtained by compounding anhydrous gypsum with the above-mentioned cement.
[0045] Furthermore, in some embodiments, the anhydrous gypsum is type II anhydrous gypsum with a mesh size of 600-1300 meshes.
[0046] According to the different hydration activities of anhydrous gypsum, anhydrous gypsum can be divided into type I, type II and type III, among which type I anhydrous gypsum only exists above 1180°C, type III anhydrous gypsum easily absorbs steam in the air and is converted into β-hemihydrate gypsum, and type II anhydrous gypsum has higher strength and hardness than hemihydrate gypsum. In the technical solution of the embodiment of the present application, the cementitious system formed by compounding type II anhydrous gypsum with cement has better strength. At the same time, the particle size of anhydrous gypsum will affect the excitation effect of the stimulator on it. If the particle size of anhydrous gypsum is too small, the hydration reaction rate will be too fast, and the crystals obtained after the hydration reaction will be small. Due to the small crystals and large specific surface area, the amount of water used in the standard consistency of slurry needs to be increased, resulting in a larger porosity after the tile adhesive is hardened, and then the strength will decrease; if the particle size of anhydrous gypsum is too large, the hydration reaction rate will be slow, and it will easily lead to the presence of unhydrated anhydrous gypsum inside the tile adhesive. The residual anhydrous gypsum will be hydrated in the later stage of the hardening of the tile adhesive, which will induce the expansion and cracking of the tile adhesive, thereby affecting the long-term performance of the tile adhesive.
[0047] Furthermore, in some embodiments, the retarder is a protein retarder; and / or the water retaining agent is a cellulose ether compound; and / or the cross-linking agent is one or more of a silane coupling agent and a titanate coupling agent.
[0048] In the technical solution of the embodiment of the present application, the retarder can slow down the hardening speed of cement and anhydrous gypsum, so that there is more sufficient operation time during construction, the water retaining agent can promote the complete hydration of anhydrous gypsum, and the cross-linking agent makes the anhydrous gypsum and cement and other additives fully combined, so that alkali and salt cannot migrate to the surface with water, thereby reducing the alkali return phenomenon.
[0049] Further, in some embodiments, the tile adhesive includes 40 parts of cement, 50 parts of anhydrous gypsum, 25 parts of beta gypsum, 5 parts of activator, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0050] In the technical solution of the embodiment of the present application, by controlling the mass ratio of cement, anhydrous gypsum, β-gypsum, activator, retarder, water retaining agent and cross-linking agent to 40:50:25:5:1.25:1.25:3.5, the tile adhesive can obtain better strength and more suitable initial and final setting time.
[0051] In a second aspect, an embodiment of the present application provides a method for preparing the tile adhesive as described in the first aspect, comprising the following steps: The anhydrous gypsum, beta gypsum, activator, retarder, water retaining agent and cross-linking agent are uniformly mixed to obtain a mixture; Mix the mixture with cement evenly to obtain tile adhesive.
[0052] In the technical solution of the embodiment of the present application, anhydrous gypsum, beta gypsum, an activator and other additives are first mixed to obtain a mixture, wherein the activator in the mixture can activate the activity of the anhydrous gypsum to make it produce cementing properties. Thereafter, after the mixture is mixed with cement, the activated anhydrous gypsum contained in the mixture can form an anhydrous gypsum-cement double-bonding material with cement, and the anhydrous gypsum-cement double-bonding material has the effects of adjusting the hardening speed of tile adhesive, improving durability, and enhancing its bonding strength with tiles.
[0053] In a third aspect, an embodiment of the present application provides an application method of the tile adhesive as described in the first aspect, comprising: uniformly mixing the tile adhesive and water to obtain a particle-free paste, and then pasting the tiles; wherein the mass ratio of the tile adhesive to water is 1:(0.2~0.6).
[0054] In the technical solution of the embodiment of the present application, the ceramic tile adhesive is mixed with water to paste the ceramic tiles, so it has the characteristics of strong bonding force and high construction efficiency. By controlling the amount of ceramic tile adhesive and water within a reasonable range, the consistency and fluidity of the mixture during mixing are guaranteed, so that the ceramic tile adhesive can not only be well bonded with the ceramic tile and the base surface during construction, but also bear the weight of the ceramic tile before initial setting without flowing or collapsing. If the amount of water used is too large and the fluidity is too high, it will be difficult for the ceramic tile to be bonded with the base surface, and a good bonding effect cannot be achieved; if the amount of water added is too low, the viscosity will be high, which may cause unevenness in the hardening process of the ceramic tile adhesive, affecting the performance and construction quality of the ceramic tile adhesive. The mass ratio of ceramic tile adhesive to water can be 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6 or other ratios within this range.
[0055] Furthermore, in some embodiments, the initial setting time of the tile adhesive during the application process is 5~30min, the final setting time is ≤180min, the original tensile bonding strength is 1.2~1.4MPa, the tensile bonding strength after immersion in water is 0.8~1.0MPa, the tensile bonding strength after heat aging is 1.1~1.3MPa, the tensile bonding strength after freeze-thaw cycles is 1.0~1.2MPa, the tensile bonding strength after airing for 20min is 0.6~0.85MPa, and the sliding distance of a 300g tile in 30 minutes is 0.15~0.25mm.
[0056] In the technical solution of the embodiment of the present application, by using the tile adhesive as described in the first aspect to paste the tiles, it has a suitable solidification time, can achieve a firm pasting effect, and has good weather resistance.
[0057] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0058] The retarder used in the following examples and comparative examples is a protein retarder purchased from Jiangsu Zhaojia, model ZJ-G18N; the water retaining agent is hydroxyethyl methylcellulose; and the cross-linking agent is silane coupling agent KH560.
[0059] 1. Preparation method Example 1 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 40 parts of sulphoaluminate cement, 50 parts of anhydrous gypsum, 25 parts of β-gypsum, 1 part of calcium oxide, 3 parts of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0060] (2) Anhydrous gypsum, β-gypsum, calcium oxide, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0061] Application method: Mix tile adhesive powder and water in a mass ratio of 1:0.5, use an electric mixer to stir until it becomes a paste without particles, and then use the paste tile adhesive to paste the tiles.
[0062] Example 2 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 40 parts of sulphoaluminate cement, 50 parts of anhydrous gypsum, 25 parts of β-gypsum, 2 parts of calcium oxide, 3 parts of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0063] (2) Anhydrous gypsum, β-gypsum, calcium oxide, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0064] Application method: Mix tile adhesive powder and water in a mass ratio of 1:0.5, use an electric mixer to stir until it becomes a paste without particles, and then use the paste tile adhesive to paste the tiles.
[0065] Example 3 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 40 parts of sulphoaluminate cement, 50 parts of anhydrous gypsum, 25 parts of β-gypsum, 3 parts of calcium oxide, 3 parts of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0066] (2) Anhydrous gypsum, β-gypsum, calcium oxide, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0067] Application method: Mix tile adhesive powder and water in a mass ratio of 1:0.5, use an electric mixer to stir until it becomes a paste without particles, and then use the paste tile adhesive to paste the tiles.
[0068] Example 4 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 40 parts of sulphoaluminate cement, 50 parts of anhydrous gypsum, 25 parts of β-gypsum, 3 parts of calcium oxide, 1 part of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0069] (2) Anhydrous gypsum, β-gypsum, calcium oxide, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0070] Application method: Mix tile adhesive powder and water in a mass ratio of 1:0.5, use an electric mixer to stir until it becomes a paste without particles, and then use the paste tile adhesive to adhere the tiles.
[0071] Example 5 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 40 parts of sulphoaluminate cement, 50 parts of anhydrous gypsum, 25 parts of β-gypsum, 3 parts of calcium oxide, 2 parts of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0072] (2) Anhydrous gypsum, β-gypsum, calcium oxide, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0073] Application method: Mix tile adhesive powder and water in a mass ratio of 1:0.5, use an electric mixer to stir until it becomes a paste without particles, and then use the paste tile adhesive to adhere the tiles.
[0074] Example 6 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 20 parts of sulphoaluminate cement, 30 parts of anhydrous gypsum, 20 parts of beta gypsum, 2 parts of calcium oxide, 2 parts of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0075] (2) Anhydrous gypsum, β-gypsum, calcium oxide, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0076] Application method: Mix tile adhesive powder and water in a mass ratio of 1:0.5, use an electric mixer to stir until it becomes a paste without particles, and then use the paste tile adhesive to adhere the tiles.
[0077] Example 7 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 30 parts of sulphoaluminate cement, 40 parts of anhydrous gypsum, 23 parts of β-gypsum, 2.5 parts of calcium oxide, 2.5 parts of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0078] (2) Anhydrous gypsum, β-gypsum, calcium oxide, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0079] Application method: Mix tile adhesive powder and water in a mass ratio of 1:0.5, use an electric mixer to stir until it becomes a paste without particles, and then use the paste tile adhesive to adhere the tiles.
[0080] Comparative Example 1 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 40 parts of sulphoaluminate cement, 50 parts of anhydrous gypsum, 25 parts of β-gypsum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0081] (2) Anhydrous gypsum, β-gypsum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0082] Comparative Example 2 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 40 parts of sulphoaluminate cement, 50 parts of anhydrous gypsum, 25 parts of β-gypsum, 5 parts of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0083] (2) Anhydrous gypsum, β-gypsum, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0084] Comparative Example 3 A tile adhesive, the preparation method of which is as follows: (1) Weigh 40 parts by mass of sulphoaluminate cement, 50 parts by mass of anhydrous gypsum, 25 parts by mass of β-gypsum, 5 parts by mass of calcium oxide, 1.25 parts by mass of retarder, 1.25 parts by mass of water retaining agent, and 3.5 parts by mass of cross-linking agent.
[0085] (2) Anhydrous gypsum, β-gypsum, calcium oxide, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0086] Comparative Example 4 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 40 parts of sulphoaluminate cement, 70 parts of anhydrous gypsum, 25 parts of β-gypsum, 2 parts of calcium oxide, 3 parts of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0087] (2) Anhydrous gypsum, β-gypsum, calcium oxide, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0088] Comparative Example 5 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 40 parts of sulphoaluminate cement, 10 parts of anhydrous gypsum, 25 parts of β-gypsum, 2 parts of calcium oxide, 3 parts of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0089] (2) Anhydrous gypsum, β-gypsum, calcium oxide, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0090] Comparative Example 6 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 60 parts of sulphoaluminate cement, 50 parts of anhydrous gypsum, 25 parts of β-gypsum, 2 parts of calcium oxide, 3 parts of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0091] (2) Anhydrous gypsum, β-gypsum, calcium oxide, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0092] Comparative Example 7 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 10 parts of sulphoaluminate cement, 50 parts of anhydrous gypsum, 25 parts of β-gypsum, 2 parts of calcium oxide, 3 parts of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0093] (2) Anhydrous gypsum, β-gypsum, calcium oxide, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0094] Comparative Example 8 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 40 parts of sulphoaluminate cement, 50 parts of anhydrous gypsum, 40 parts of β-gypsum, 2 parts of calcium oxide, 3 parts of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0095] (2) Anhydrous gypsum, β-gypsum, calcium oxide, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0096] Comparative Example 9 A tile adhesive, the preparation method of which is as follows: (1) By mass, weigh 40 parts of sulphoaluminate cement, 50 parts of anhydrous gypsum, 10 parts of β-gypsum, 2 parts of calcium oxide, 3 parts of alum, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
[0097] (2) Anhydrous gypsum, β-gypsum, calcium oxide, alum, retarder, water retaining agent and cross-linking agent are mixed and stirred uniformly to obtain a mixture; then the mixture is mixed and stirred uniformly with cement to obtain tile adhesive powder.
[0098] 2. Test Method The tile adhesives of Examples 1-6 and Comparative Examples 1-9 were applied to tiles, and their initial setting time, final setting time and adhesive strength were tested; (1) Initial setting and final setting time: The initial setting time is measured from the time the tile adhesive is added. If the indentation test does not show obvious marks, it indicates that the tile has already set initially. The time consumed is the initial setting time. The final setting time is the time required for the tile adhesive to completely lose its plasticity and begin to generate strength.
[0099] (2) Adhesive strength: Test the adhesive tensile strength after complete solidification according to JC / T547-2017 "Ceramic Wall and Floor Tile Adhesive".
[0100] (3) Anti-slip performance: The anti-slip performance of the tiles was tested using the GB / T26542-2011 tilting platform method; the displacement distance of a 300g tile in 30 minutes.
[0101] III. Analysis of test results of various embodiments and comparative examples Table 1 Composition of tile adhesives in Examples and Comparative Examples (parts)
[0102] Table 2 Performance test results of tile adhesive in embodiments and comparative examples
[0103] As shown in Table 2, the tile adhesive provided by the present invention has a short setting time, and the time when it completely loses plasticity and begins to generate strength is less than 24h, which greatly shortens the paving period of tiles. Among them, the initial setting time of the tile adhesive in Example 1, Example 2, Example 4 and Example 6 is ≥20min. Compared with Example 3, Example 5 and Example 7, the time for construction operation is more sufficient, which is more conducive to practical operation. At the same time, when it is quickly solidified, the adhesive tensile strength of the tile adhesive is relatively high, between 1.2~1.4MPa, the tensile bonding strength after immersion in water is 0.8~1.0MPa, the tensile bonding strength after heat aging is 1.1~1.3MPa, the tensile bonding strength after freeze-thaw cycle is 1.0~1.2MPa, the tensile bonding strength after 20min of airing is 0.6~0.85MPa, and the sliding distance of 300g tiles in 30 minutes is 0.15~0.25mm, which meets the technical requirements of "JC / T547-2017 Ceramic Wall and Floor Tile Adhesive" and has good product quality.
[0104] It can be seen from Examples 1 to 3 that calcium oxide affects the initial and final setting time. When the amount of alum is constant, the initial and final setting time decreases with the increase of calcium oxide. Among them, the initial setting time of Example 2 is greater than 20 minutes, and the final setting time is less than 120 minutes, which not only ensures sufficient construction operation time in the early stage, but also can solidify quickly after construction, and its bonding strength is basically unaffected. It can be seen from Examples 3 to 5 that when the calcium oxide content is constant, the initial setting time and the final setting time are shortened with the increase of alum content, among which the construction operation time of Example 4 is longer.
[0105] Comparing Comparative Example 1 with Example 2, it can be seen that the activator has an effect on both the initial and final setting times, indicating that the activator can promote the transformation of anhydrous gypsum into a cementitious material; at the same time, the activator also affects the bonding strength and weather resistance of the tile adhesive.
[0106] Comparison of Comparative Examples 2 to 3 with Example 2 shows that calcium oxide and alum have significant effects on the initial and final setting time; calcium oxide mainly affects the initial setting time, which can ensure that the construction has sufficient operation time, and alum mainly affects the final setting time, so that the tiles solidify quickly after pasting. At the same time, it can be seen that the present invention can not only obtain better initial and final setting time by compounding calcium oxide and alum, but also the tile adhesive has a good bonding effect.
[0107] Comparing Comparative Examples 4 to 5 with Example 2, it can be seen that excessive use of anhydrous gypsum will lead to prolonged setting time and decreased bonding strength, because too much anhydrous gypsum cannot be fully hydrated; if the amount of anhydrous gypsum is too little, the hydration rate will be too fast, thereby reducing the initial setting time, and basically has no effect on bonding strength and weather resistance.
[0108] Comparing Comparative Examples 6-7 with Example 2, it can be seen that too much cement will increase the initial and final setting time, while too little cement will shorten the initial setting time and slightly increase the final setting time; at the same time, too much or too little cement will reduce the bonding strength.
[0109] Comparing Comparative Examples 8-9 with Example 2, it can be seen that too much β-gypsum shortens the initial setting time and has little effect on the final setting time, while too little β-gypsum significantly increases both the initial and final setting times, which is not conducive to rapid solidification and affects the bonding strength of the tile adhesive.
[0110] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A tile adhesive, characterized in that: Calculated by mass, it includes 20-40 parts of cement, 30-50 parts of anhydrous gypsum, 20-25 parts of beta gypsum, 4-6 parts of activator, 0.5-2 parts of retarder, 0.5-2 parts of water retaining agent and 2-6 parts of cross-linking agent; wherein the activator includes calcium oxide and alum.
2. The tile adhesive according to claim 1, characterized in that: The mass ratio of the calcium oxide to the alum is (1-5): (1-5).
3. The tile adhesive according to claim 2, characterized in that: The mass ratio of the calcium oxide to the alum is 2:
3.
4. The tile adhesive according to claim 1, characterized in that: The cement is one or more of sulphoaluminate cement, silicate cement and aluminate cement.
5. The tile adhesive according to claim 1, characterized in that: The anhydrous gypsum is type II anhydrous gypsum with a mesh size of 600-1300 meshes.
6. The tile adhesive according to claim 1, characterized in that: The retarder is a protein retarder; and / or The water retaining agent is a cellulose ether compound; and / or The cross-linking agent is one or more of a silane coupling agent and a titanate coupling agent.
7. The tile adhesive according to claim 1, characterized in that: In parts by mass, the tile adhesive includes 40 parts of cement, 50 parts of anhydrous gypsum, 25 parts of beta gypsum, 5 parts of activator, 1.25 parts of retarder, 1.25 parts of water retaining agent, and 3.5 parts of cross-linking agent.
8. A method for preparing the tile adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: The anhydrous gypsum, beta gypsum, activator, retarder, water retaining agent and cross-linking agent are uniformly mixed to obtain a mixture; The mixed material is evenly mixed with cement to obtain tile adhesive.
9. An application of the tile adhesive according to any one of claims 1 to 7, characterized in that: The tile adhesive and water are uniformly mixed to obtain a particle-free paste, and then the tiles are pasted; wherein the mass ratio of the tile adhesive to water is 1: (0.2-0.6).
10. The use of the tile adhesive according to claim 9, characterized in that: The initial setting time of the tile adhesive during application is 5 to 30 minutes, the final setting time is ≤180 minutes, the original tensile bonding strength is 1.2 to 1.4 MPa, the tensile bonding strength after immersion in water is 0.8 to 1.0 MPa, the tensile bonding strength after heat aging is 1.1 to 1.3 MPa, the tensile bonding strength after freeze-thaw cycles is 1.0 to 1.2 MPa, the tensile bonding strength after airing for 20 minutes is 0.6 to 0.85 MPa, and the sliding distance of a 300g tile in 30 minutes is 0.15 to 0.25 mm.
Citation Information
Patent Citations
Wall material composite material
CN111302751A
Lightweight high-toughness phosphorus II type anhydrous gypsum-based wallboard and preparation method thereof
CN116947443A
High-adhesion waterproof gypsum tile adhesive and preparation method thereof
CN118652096A
Cement chip board
JP1995048165A
Quick-hardening agent and quick-hardening cement composition
JP2013095624A